ANALYSIS OF FACTORS INFLUENCING MILLENNIAL AND GEN Z EMPLOYEE ENGAGEMENT IN A GLOBAL WORK ENVIRONMENT - Ananda Fitriani Dewi; Zainuddin, Zainuddin; Efendi Pakpahan (Jurnal Cakrawala Ilmiah, 2025)
This study aims to analyze the factors influencing the engagement of Millennial and Generation Z employees within the complex and multicultural context of the global work environment. Employing a quantitative approach with a survey method, data were collected from 400 respondents working in multinational organizations with operations across various countries. Multiple regression analysis revealed that Global Career Development, Global Work Flexibility, Global Inclusive Culture, Adaptive Global Leadership, Global Technology and Virtual Collaboration, and Global Meaning and Impact of Work significantly affect Global Employee Engagement (Adjusted R Square =0.781, F(6,393)=238.472, p<0.001). Among these factors, Adaptive Global Leadership (β = 0.321) had the strongest influence, followed by Global Inclusive Culture (β = 0.268) and Global Meaning and Impact of Work (β = 0.230). These findings underscore the importance of a holistic approach in global talent management that considers various aspects of the work experience to enhance the engagement of young employees. This research provides valuable insights and evidence-based recommendations for multinational organizations in designing more effective strategies to foster the engagement of Millennials and Generation Z, ultimately contributing to sustainable competitive advantage